Heat and Hypoxia Exposure Mediates Circadian Rhythms Response via Methylation Modification in Apostichopus japonicas - Wu, Jiong; Zhang, Weiwei; Li, Chenghua (Frontiers in Marine Science, 2021)
As global warming progresses, heat and hypoxia are gradually becoming important factors threatening the survival, reproduction and development of marine organisms. To determine the effect of heat and hypoxia on Apostichopus japonicus, whole genome methylation of the respiratory tree was determined under heat, hypoxia, and heat-hypoxia conditions (designed as HT, LO and HL groups). The number of differentially methylated regions (DMRs) under three treatments was determined based on the Venn diagram. Network of the DMRs associated with promoter that were co-existed under the three conditions showed that circadian rhythm was involved based on Kyoto Encyclopedia of Genes and Genomes analyses. Circadian rhythm related genes, CRY1a, CRY1b, CLC and TIM, decreased in LO and HL groups, while CRY1a, CRY1b, and BMAL1 increased in the HT group. BSP combined with PCR showed that the methylation levels of CpG island in promoters of CRY1a and CRY1b were up-regulated in HT, LO and HL groups, leading to the decreased promoter activity of CRY1a and CRY1b. RNAi of CRY1a and CRY1b led to increased enzyme activities of two energy related enzymes, pyruvate kinase (PK) catalyzing the rate-limiting step in glycolysis, and ATPase hydrolyzing ATP to ADP, which were also increased under the three tested conditions. Thus, it was concluded that A. japonicus may respond to the heat, hypoxia, and heat-hypoxia stresses via the DNA methylation of circadian rhythm CpG island, which increases the activity of energy-related enzymes.